2021
DOI: 10.1101/2021.08.25.457683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid gene evolution in an ancient post-transcriptional and translational regulatory system compensates for meiotic X chromosomal inactivation

Abstract: It is conventionally assumed that conserved pathways evolve slowly with little participation of gene evolution. Nevertheless, it has been recently observed that young genes can take over fundamental functions in essential biological processes, for example, development and reproduction. It is unclear how newly duplicated genes are integrated into ancestral networks and reshape the conserved pathways of important functions. Here, we investigated origination and function of two autosomal genes that evolved recent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 99 publications
(129 reference statements)
1
6
0
Order By: Relevance
“…The CAZAM frequency of both Dmel_Zeus ChIP-Seq genes and Dsim_Zeus ChIP-Seq genes shows a drastic fluctuation ( Figure 5 D). Taken together, we speculate that Zeus exhibits a rapid, dynamic and species-differential coevolution with specific motif for its neofunctionalization, as is consistent with what we recently observed [ 13 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The CAZAM frequency of both Dmel_Zeus ChIP-Seq genes and Dsim_Zeus ChIP-Seq genes shows a drastic fluctuation ( Figure 5 D). Taken together, we speculate that Zeus exhibits a rapid, dynamic and species-differential coevolution with specific motif for its neofunctionalization, as is consistent with what we recently observed [ 13 ].…”
Section: Resultssupporting
confidence: 92%
“…To test this, we generated Zeus loss-of-function lines by using CRISPR-Cas9 (see Methods section and Figure 5 A). We found that the KO lines had significantly reduced (22%) viability ( p < 0.05, t-test) [ 13 ], suggesting an important functional role of Zeus. We further conducted RNA-Seq on adult male whole testes, in which Zeus is normally expressed, from control injection and Zeus knockout (KO) lines in biological triplicate.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations